Answer:-7
Step-by-step explanation:Let's solve your equation step-by-step.
3(3x+1)−(4x+1)=6x−3(x+4)
Step 1: Simplify both sides of the equation.
3(3x+1)−(4x+1)=6x−3(x+4)
3(3x+1)+−1(4x+1)=6x−3(x+4)(Distribute the Negative Sign)
3(3x+1)+−1(4x)+(−1)(1)=6x−3(x+4)
3(3x+1)+−4x+−1=6x−3(x+4)
(3)(3x)+(3)(1)+−4x+−1=6x+(−3)(x)+(−3)(4)(Distribute)
9x+3+−4x+−1=6x+−3x+−12
(9x+−4x)+(3+−1)=(6x+−3x)+(−12)(Combine Like Terms)
5x+2=3x+−12
5x+2=3x−12
Step 2: Subtract 3x from both sides.
5x+2−3x=3x−12−3x
2x+2=−12
Step 3: Subtract 2 from both sides.
2x+2−2=−12−2
2x=−14
Step 4: Divide both sides by 2.
2x /2
=
−14 /2
x=−7